2020
DOI: 10.1186/s12905-020-01116-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of breast lesions diagnosed by cytology examination in symptomatic patients at Eritrean National Health Laboratory, Asmara, Eritrea: a retrospective study

Abstract: Background Fine needle aspiration cytology is a simple, relatively accurate, non-invasive, and cost-effective method of diagnosing most breast pathologies. To date, there is no sufficient data depicting the distribution of breast lesions detected by fine needle aspiration cytology in our healthcare setting. The aim of this study was to elucidate the general distribution of breast lesions diagnosed by cytology test at Eritrean National Health Laboratory. Methods This retrospective study was carried out on 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
4
5
0
Order By: Relevance
“…Additionally, the mean age of presentation was significantly higher for patients with malignancies than for those with benign lesions. This finding is similar to that of other studies performed by Rioki et al (16), Madan et al (15), Embaye et al (13) and Khanam et al (1), as they also reported the maximum incidence of cases in younger (<30 years) age group. However, the study by Singh and Tyagi (17) reported that patients aged 31 to 40 years had the most cases of breast lumps.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the mean age of presentation was significantly higher for patients with malignancies than for those with benign lesions. This finding is similar to that of other studies performed by Rioki et al (16), Madan et al (15), Embaye et al (13) and Khanam et al (1), as they also reported the maximum incidence of cases in younger (<30 years) age group. However, the study by Singh and Tyagi (17) reported that patients aged 31 to 40 years had the most cases of breast lumps.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the number of female patients was higher than that of male patients, with a male to female ratio of 59.2:1, which was higher than 26:1 and 4:1, as reported by Embaye et al (13) and Qadri et al, respectively (14). Overall, the mean age of the patients was slightly lower in the present study than in the studies by Embaye et al (13) (mean age, 33.05 years) and Madan et al (15) (mean age 34.54 years).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is consistent with the findings of Embaye et al . (40%) [ 8 ] but relatively lower (53.61%, and 56.2%) than that observed in other studies [ 3 , 9 , 23 ]. On the contrary, fibrocystic disease was the most common detected by Kumar [ 29 ].…”
Section: Discussionmentioning
confidence: 59%
“…The triple test approach (physical examination, radiology, and cytopathology) is used in the evaluation of breast lesions. Fine needle aspiration cytology (FNAC), one of the “triple test” approaches for evaluating breast lumps distinguish neoplastic and non-neoplastic lesions of the breasts [ 7 , 8 ]. This technique is rapid, reliable, highly acceptable by patients, cost-effective, and has low complication rates [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%